Evaluasi Sarana Evakuasi Bangunan Gedung di Kantor Dinas Tenaga Kerja Kabupaten Gresik - Ade Yusuf Fatahillah; Moch. Sahri; Merry Sunaryo; Muslikha Nourma Rhomandoni (Peneliti.net, 2022)
Evacuation Facility is a continuous and unobstructed passageway from any point in the building to the road, yard, field or other open space that provides access to public roads. This study aims to evaluate the means of evacuating buildings at the Gresik Regency Manpower Office. This research is a type of qualitative research with descriptive observational method. The population of this research is the office building of the Gresik Regency Manpower Office. data collection using observation sheets and roll meters as measuring tools. The sampling technique used was the total sample. The results of the study showed that several aspects of the evacuation facilities in the Gresik district manpower office building were found to have no markers on exit access in each building, there were no markers and some provisions for exit doors in each building, were found to be inappropriate in the exit release area in the building. to the south which is used as a parking lot for 2-wheeled and 4-wheeled motorized vehicles, no evacuation plan has been found and there is no marker used as a gathering point. The conclusion of this study is that building evacuation facilities according to the Regulation of the Minister of Public Works and Public Housing Number 14 of 2017 concerning the requirements for building facilities are still found to be incompatible with exit access, exit, exit release, evacuation plans and assembly points. Recommendations that can be given are to draw up markers to show exit and exit access, rearrange the parking area so that exit releases are not obstructed, draw up evacuation plans and provide markers at the gathering point area.